THE BRAVERY ACT OF MINNY JACKSON AND AIBILEEN CLARK IN THE HELP NOVEL BY KATRHRYN STOCKETT - Vinka Andriani; Rezky Khoirina Tarihoran; Ratna Sari Dewi (PHILOLOGY Journal of English Language and Literature, 2023)
This study aims to describe the elements of the novel which include the plot, characters and characterizations, as well as the setting in The Help by Kathryn Stockett, then to describe the acts of courage of Minny Jackson and Aibileen Clark. This research is a qualitative descriptive using a feminist approach. The results of this study are as follows. (1) The theme of slavery. The two main characters of the black race. Both have different characters. Background in the City of Jackson, Mississippi in the 60's circa 1962 to 1963. (2) Acts of courage Minny Jackson and Aibileen Clark in The Help by Kathryn Stockett.